Efficacy of Different Types of Exercise-Based Cardiac Rehabilitation on Coronary Heart Disease: a Network Meta-analysis - Xia, Tian-li (J Gen Intern Med, 2018)
BACKGROUND: Exercise-based cardiac rehabilitation (CR) has been recognized as an essential component of the treatment for coronary heart disease (CHD). Determining the efficacy of modern alternative treatment methods is the key to developing exercise-based CR programs. METHODS: Studies published through June 6, 2016, were identified using MEDLINE, EMBASE, and the Cochrane Library. English-language articles regarding the efficacy of different modes of CR in patients with CHD were included in this analysis. Two investigators independently reviewed abstracts and full-text articles and extracted data from the studies. According to the categories described by prior Cochrane reviews, exercise-based CR was classified into center-based CR, home-based CR, tele-based CR, and combined CR for this analysis. Outcomes included all-cause mortality, cardiovascular death, recurrent fatal and/or nonfatal myocardial infarction, recurrent cardiac artery bypass grafting, recurrent percutaneous coronary intervention (PCI), and hospital readmissions. RESULTS: Sixty randomized clinical trials (n = 19,411) were included in the analysis. Network meta-analysis (NMA) demonstrated that only center-based CR significantly reduced all-cause mortality (center-based: RR = 0.76 [95% CI 0.64–0.90], p = 0.002) compared to usual care. Other modes of CR were not significantly different from usual care with regard to their ability to reduce mortality. Treatment ranking indicated that combined CR exhibited the highest probability (86.9%) of being the most effective mode, but this finding was not statistically significant due to the small sample size (combined: RR = 0.50 [95% CI 0.20–1.27], p = 0.146). CONCLUSIONS: Current evidence suggests that center-based CR is acceptable for patients with CHD. As home- and tele-based CR can save time, money, effort, and resources and may be preferred by patients, their efficacy should be investigated further in subsequent studies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-018-4636-y) contains supplementary material, which is available to authorized users.